Why people die of active tuberculosis in the era of effective chemotherapy in Southern Ethiopia: A qualitative study. (December 2022) - Shegaze, Mulugeta; Boda, Belay; Ayele, Gistane; Gebremeskel, Feleke; Tariku, Befikadu; Gultie, Teklemariam
Abstract: Background: High TB mortality is increasingly understood as an indicator of different problems in the health system and community. Limited awareness of TB in the community, restricted accessibility and/or quality of health services can hamper survival. Exploration and analysis of death among TB patients can lead to a clearer and specific understanding of why the deaths happened and where interventions are likely to make a difference in a specific context. Objective: The study aimed to assess why people die of active tuberculosis in the era of effective chemotherapy. Methods: The study was conducted from October to December 2020 in Arba Minch Health and Demographic Surveillance System (AM-HDSS) by applying phenomenological study design. A total of 27 family members of people who had died of TB, 9 health extension workers (HEW) and 8 health care professionals working in TB clinics were participated in open in-depth interview. A total of 130 individuals participated in 16 focus group discussion which composed of patient survived from TB, religious leader, health development army (HAD) and HEWs. Adequacy of information (saturation) was considered as an adequate sample size to create the intended qualitative product. All the interviews and FGD were tape recorded and recordings were transcribed immediately. ATLAS TI 9 software was used to analyse and process qualitative data. From data set codes were created then by identifying pattern among them themes were created. Then, generated themes were compared and some of them were split, combined, discarded and new ones created after returning to data set. Finally, themes were defined and a concise and easily understandable name was given for each theme. Result: Luck of sufficient knowledge about TB was considered to be a reason for cause of death. Most of the time, TB patients underestimate and ignore when the symptoms first emerge and will not relate it with any diseases. The low level of community awareness about the cause, transmission, treatment and prevention highly contributed to increased transmission rate and death due to TB. The study identified misconceptions in the community; they prefer traditional medicine to the scientific way. First, they try different herbal medicine to get relief from their illness. At the end, if the disease is getting worse, they visit health facilities. Participants mentioned high transportation cost, poor health seeking behaviours, inadequate food consumption and lack of TB awareness as reasons for low treatment adherence. The health facilities were inaccessible for the community. Most of them indicated that health facilities were too far to reach. In some health institution, right amount and combination of medication were not delivery on time and Diagnostic facilities for TB were reported to be inadequate. Conclusion: Poor treatment adherence, lack of TB awareness, stigma, inadequate food consumption, poor health care seeking behaviour and inaccessibility of health facility were identified as major reasons for death. To prevent death of TB patients all sectors such as education, health, and agriculture should work to address health education, infrastructures, nutritional supplementation needs of TB patients, caregivers and the community as a whole.